Black Press, White Press, and Their Opposition: The Case of the Police Killing of Tyisha Miller - Huspek, Michael (Social justice, 2004)
Part of a special issue on resisting militarism and globalized punishment. The oppositional thesis is used to examine differences in the way that two newspapers covered the 1998 police killing of Tyisha Miller, a 19-year-old African-American woman. The oppositional thesis contends that the black and white presses are not merely different, but are oppositional. The two newspapers are the Riverside Press-Enterprise, a mainstream daily with a predominantly white readership, and the Black Voice News, a weekly publication with a predominantly black readership.